Effect of agricultural lands afforestation and tree species composition on the soil reaction, total organic carbon and nitrogen content in the uppermost mineral soil profile - Ondřej HOLUBÍK; Vilém PODRÁZSKÝ; Jan VOPRAVIL; Tomáš KHEL; Jiří REMEŠ (Soil and Water Research, 2014)
Forests occupy one third of the world's land area and govern carbon (C) transfers and influence nitrogen (N) content in the biosphere. Afforestation leads to soil changes of specific dynamics, often accompanied by acidification. Especially at higher altitudes this effect is accelerated and increased with the stand age since forestation. The change in soil C and N content following afforestation is controlled by a number of factors, including: previous land use (grasslands, cropland, etc.), tree species, soil cultivation method, soil properties (clay content, pH), stand age, site management, topography, and climate. In the Czech Republic, large area changes in land use took place in the last centuries - forests covering roughly 20% in the 18th century currently occupy almost 34%, with still increasing tendencies. This paper compares basic soil properties (soil reaction, total soil organic carbon as well as total nitrogen contents) of the agricultural land and land afforested 40-60 years ago. The results confirmed the key role of afforestation in the change of soil organic matter dynamics after establishing new forests on the former agricultural lands in the uppermost mineral soil part of the Orlické hory Mts. region in the Czech Republic. During that time, comparatively substantial changes in soil organic matter and nitrogen were registered. Afforestation considerably increased organic matter content in the studied A-horizons of different land use types. Soil development resulted in a high production of C and N pools under the forest stands, contrary to agricultural land. In general, afforestation caused significant soil acidification. The common tendency of higher acidity of forest soils compared to agricultural ones was documented in the studied case as well. The general tendencies of soil reaction and soil organic matter dynamics at the studied sites are comparable to those in other regions of the Czech Republic.